1997
DOI: 10.2116/analsci.13.supplement_59
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Oxovanadium(IV) Acetylacetonate on the Chemiluminescence Reaction of Luminol in Reverse Micelles.

Abstract: Higashi-Upon mixing of oxovanadium(IV) acetylacetonate, this complex caused an increase in the chemiluminescence (CL) of luminol in a reverse micellar medium of cetyltrimethylammonium chloride in chloroform-cyclohexane (6:5 vlv)-water (buffered with NaOH-Na2C03, pH 12.5) even in the absence of an oxidizing reagent such as hydrogen peroxide. In this CL process, the reaction of Luminol with the oxovanadium(IV) ion produced from the decomposition of the oxovanadium(IV) complex in the reverse micelles is probably … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
24
1

Year Published

1998
1998
2010
2010

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 3 publications
3
24
1
Order By: Relevance
“…Visible absorption measurements showed that increasing the concentration of sodium hydroxide in the reversed micellar solution caused a decrease in the absorbance of the complex, indicating decomposition of the complex, in which attack of nucleophilic hydroxide ion to the central metal of the complex may play an essential role at the surfactant-water pool interface of the CTAC reverse micelle; the free iron(III) ion produced is considered to be available for the CL catalysis. In our previous work 11 , a similar behavior of the oxovanadium(IV) acetylacetonate complex in the RMM-CL reaction was observed; it has been pointed out that the free VO 2 + ion produced transiently from decomposition of the complex upon its uptake by the reverse micelles may play an important part in the RMM-CL process.…”
Section: In Reverse Micellessupporting
confidence: 68%
See 2 more Smart Citations
“…Visible absorption measurements showed that increasing the concentration of sodium hydroxide in the reversed micellar solution caused a decrease in the absorbance of the complex, indicating decomposition of the complex, in which attack of nucleophilic hydroxide ion to the central metal of the complex may play an essential role at the surfactant-water pool interface of the CTAC reverse micelle; the free iron(III) ion produced is considered to be available for the CL catalysis. In our previous work 11 , a similar behavior of the oxovanadium(IV) acetylacetonate complex in the RMM-CL reaction was observed; it has been pointed out that the free VO 2 + ion produced transiently from decomposition of the complex upon its uptake by the reverse micelles may play an important part in the RMM-CL process.…”
Section: In Reverse Micellessupporting
confidence: 68%
“…[8][9][10][11] In our previous work 8 it was observed that the uptake of the iron(III) complex of 8-quinolinol (oxine), Fe(oxine) 3 , by a reverse micelle of cetyltrimethylammonium chloride (CTAC) into the water pool and its subsequent conversion into a reactive species, that is, iron(III) ion capable of catalyzing the CL reaction of luminol with hydrogen peroxide occur.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The FI system reported in our previous paper 14 has been used to carry out the flow CL measurements: the multicomponent instrument was composed of a Hitachi (Tokyo) Model K-1000 flow injection analyzer, equipped with a 16-port rotary, programmed automatic injection valve, a Tosoh (Tokyo) Model CCPM computer-controlled pump unit, and a Niti-on (Funahashi) Model LF-800 photometer with a coiled 70-mm 3 The solutions of sample and reversed micellar luminescence reagent were sucked into their respective loops of 100 mm 3 , then simultaneously inserted into the carrier streams of chloroform using the automatic rotary injection valve. The carrier flow rates of 2 cm 3 min -1 were used to drive both the sample and reagent streams through the FI system, as reported previously.…”
Section: Apparatusmentioning
confidence: 99%
“…The carrier flow rates of 2 cm 3 min -1 were used to drive both the sample and reagent streams through the FI system, as reported previously. 14 The intensity of CL emission was taken as the difference in the observed peak heights for the analyte and the blank, although the blank CL emission by luminol alone in the reversed micellar solution was very faint.…”
Section: Apparatusmentioning
confidence: 99%